A study on the antimicrobial usage pattern for the prevention of surgical site infections in a teaching hospital - K., Rajkumar (International Surgery Journal, 2019)
Background: Wrong antimicrobial selection and usage increase the incidence of drug resistance, drug toxicity and superinfections, thus decreasing the quality of healthcare delivery. Various approaches for rationalizing the antimicrobial usage have been recommended. Understanding the existing antimicrobial usage pattern is suggested as the first step in this approach, which would help to understand the current issues and to find the solution. The aim of the study was to evaluate the usage pattern of antimicrobial prophylaxis in surgical patients, to identify any inappropriateness of the usage. Methods: A retrospective evaluation of the randomly selected 258 medical records of general surgical cases for eight months in a tertiary care teaching hospital were verified for the appropriateness of the antimicrobial prophylaxis. The collected data was studied, and conclusions were drawn with the help of appropriate statistics. Results: All the 262 (100%) patients received a third generation cephalosporin through the intravenous route as a prophylactic dose. Also, 92 (35%) patients received nitroimidazole or aminoglycosides in addition to the cephalosporins. The antimicrobials were administered half an hour to one hour before the surgery. No intraoperative redosing was given. Conclusions: The timing of administration of the preoperative dose was at par with international guidelines and well allotted to the nursing staff. The intraoperative dose was appropriately omitted in the short term surgeries. The main concern was the increasing use of the third generation cephalosporins and the long duration of the postoperative prophylaxis, which required to be addressed.